Faktor Risiko Penyelenggaraan Infrastruktur Daerah dengan Skema KPBU Availability Payment - Dian Sari; Rizal Z Tamin; Iris Mahani; Andreas Wibowo (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2026)
Regional infrastructure is the backbone of the economy and public services, but local governments often face fiscal capacity constraints. Public-Private Partnership (PPP) with the Availability Payment (AP) scheme emerges as a solution to overcome the funding gap. However, its implementation at the regional level still faces a high rate of project failures. This study aims to develop a framework of critical risk factors in the implementation of regional PPP AP to improve risk management effectiveness. Using a systematic literature review approach on 38 scientific articles and operational reference documents, the study identifies 35 risk factors categorized into 10 main groups. The analysis results show that the risk landscape of regional PPP AP is dominated by governance and institutional challenges, with three main vulnerable areas: (1) AP Payment Risk (uncertainty of government commitment and fiscal capacity), (2) Political Risk (policy instability due to local political dynamics), and (3) Interface Risk (limitations in government coordination capacity and human resources). The framework provides a foundational tool for stakeholders to develop risk mitigation strategies and practical guidelines, supporting more effective and sustainable regional infrastructure development.